From traditional learning to media apprehension - Soto Ocampo, Frank (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Students, teachers and citizens know the truths and realities through media products, with aggravating circumstances such as misrepresentation, falsification, spectacularization and decontextualization. The general objective of this research is to analyze the developments, approaches and challenges of the use and appropriation of technology - communication - education interaction for media comprehension in the virtual or face-to-face classroom. In this research it was found that educational systems today raise media literacy and revive educommunication without considering that technology says how, what and why it should be apprehended.